Evaluation of the relationship between serum levels of VEGF and sVEGFR1 with mortality and prognosis in patients with Crimean–Congo hemorrhagic fever. Issue 10 (19th July 2013) - Bakir, Mehmet; Bakir, Sevtap; Sari, Ismail; Celik, Veysel Kenan; Gozel, Mustafa Gokhan; Engin, Aynur
Abstract The most accepted view to explaining the pathogenesis of Crimean–Congo hemorrhagic fever (CCHF) is endothelial damage. This study was conducted in a University hospital to investigate the serum levels and prognostic significance of the vascular endothelial growth factor (VEGF) and its receptor, soluble fms‐like tyrosine kinase‐1 receptor (sVEGFR‐1) in CCHF. Forty‐eight consecutive hospitalized CCHF patients (grouped into severe illness and non‐severe illness) and 40 healthy adults, as controls were enrolled. There was statistically significant difference for each of VEGF (P = 0.003), and sVEGFR1 (P = 0.0001) between the patients and controls. VEGF and sVEGFR1 levels in patients with severe CCHF were found to be higher than in the control group (P = 0.0001 and P = 0.0001, respectively). A significant difference was found in VEGF (P = 0.003) and sVEGFR1 (P = 0.0001) levels when compared to patients with CCHF who died and who recovered. In patients in the group with severe illness, the sensitivity, specificity, and the area underneath the ROC curve (AUROC) belonging to those cut‐off points of VEGF and sVEGFR1 were 66.7%, 76.2%, 0.747, and 77.8%, 81%, 0.849, respectively. In non‐survivors, the sensitivity, specificity, and the AUROC belonging to those cut‐off points of VEGF and sVEGFR1 defined as 77.8%, 76.9%, 0.813, and 88.9%, 97.4%, 0.912, respectively. In conclusion, high sensitivity, specificity, and the AUROC values were found in sVEGFR1 levels especially in the severely ill and non‐survivors. Therefore, sVEGFR1 may be an important biomarker for determining the risk of severity and death as result of infection with CCHF virus. J Med. Virol. 85:1794–1801, 2013. © 2013 Wiley Periodicals, Inc.